CENTRIFUGAL COMPRESSOR EFFICIENCY CALCULATION WITH HEAT TRANSFER - Dragan, Valeriu (IIUM Engineering Journal, 2017)
In this paper we present a case study of apparent performance variation of an optimized centrifugal compressor design when its metal parts are cold - before the conjugated heat transfer between the fluid and parts reaches an energetic equilibrium. The methods used are numerical, using full viscous 3D computational fluid dynamics with heat transfer. Three cases were considered, an adiabatic wall baseline, an all-blade cooling at 293 K and a more realistic stator row cooling at 293 K. Results indicate an apparent yet erroneous isentropic efficiency reading increase beyond 100% - which was to be expected due to the fluid cooling. However the isentropic and polytropic efficiencies could be estimated and were used to more accurately assess the performance of the compressor. Power consumption decreased to approximately 97% of the original load while the pressure ratio was marginally increased. This alone does not, however, explain the non-physical efficiency readings, which are mainly due to the assumptions and manner under which the efficiency itself is calculated. The paperÂ  presents a more robust approach to measuring efficiency, regardless of the heat transfer within the turbomachinery itself. Possible applications of the study may range from cold-start regime simulation to the optimization of inter-cooling setup or even flow angle control without mechanically actuated OGV